EXPO2013: a kit of tools for phasing crystal structures from powder data. (3rd July 2013) - Altomare, Angela; Cuocci, Corrado; Giacovazzo, Carmelo; Moliterni, Anna; Rizzi, Rosanna; Corriero, Nicola; Falcicchio, Aurelia
<x xml:space="preserve">Abstract</x> EXPO2013, the heir of EXPO2009, has been enriched by a variety of new algorithms and graphical tools aiming at strengthening the individual steps of the powder structure solution pathway. Particular attention has been addressed to the procedures devoted to improving structural models provided by direct methods in ab initio approaches. In addition, a new procedure has been implemented, working in direct space, which may be chosen by the user as an alternative to the traditional simulated annealing algorithm.